2009
DOI: 10.2174/1874467210902010001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Non-Opioid Analgesics Beyond Cyclooxygenase Enzyme Inhibition

Abstract: Non-opioid analgesics including both selective and non-selective cyclooxygenase (COX) inhibitors and acetaminophen are the most widely used treatments for pain. Inhibition of COX is thought to be largely responsible for both the therapeutic and adverse effects of this class of drugs. Accumulating evidence over the past two decades has demonstrated effects of non-opioids beyond the inhibition of COX and prostaglandin synthesis that might also explain their therapeutic and adverse effects. These include their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 205 publications
3
45
0
Order By: Relevance
“…Surgery leads to a complex systemic response in plasma PGE2 and IL-6 despite perioperative neuronal blockade. May Hazma et al [8] have reported downregulation of gene and protein expression of phosphodiesterase type IV enzyme by rofecoxib and ketorolac in oral mucosal biopsies 3 h after third molar tooth extraction. NFjB also plays an important role in the upregulation of IL-6 in response to several inflammatory mediators.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery leads to a complex systemic response in plasma PGE2 and IL-6 despite perioperative neuronal blockade. May Hazma et al [8] have reported downregulation of gene and protein expression of phosphodiesterase type IV enzyme by rofecoxib and ketorolac in oral mucosal biopsies 3 h after third molar tooth extraction. NFjB also plays an important role in the upregulation of IL-6 in response to several inflammatory mediators.…”
Section: Resultsmentioning
confidence: 99%
“…AQAH and CHAH caused a significant dose-dependent decrease in the number of acetic acid-induced writhes in comparison to control. This observation indicates that AQAH and CHAH could possess peripherally-mediated antinociceptive property and AQAH and CHAH induced analgesic effect through different mechanisms and at different levels linked to inhibition of prostaglandin synthesis, L-arginine-nitric oxide-cyclic GMP-ATP-sensitive K+ channel cascade, serotonergic pathway, cholinergic pathway, adrenergic pathway, inhibition of cytokine production and others [30] . The formalin test is used to identify mainly centrally acting agents, which inhibit both early and late phase responses almost equally.…”
Section: Resultsmentioning
confidence: 89%
“…The use of the antidepressant drug, hyperforin, the principal constituent of St. John's wort that acts by inhibiting prostaglandin synthe- sis, [25] strengthens the above findings. Studies have demonstrated that aspirin and other non-opioid derivatives involve antinociception through monoamines like serotonin [62]. Furthermore, the latest developments advocate that aspirin reduces the risk of depression in individuals with high plasma homocysteine [63]; at cellular levels, it inhibits hippocampal neuronal loss and aberrant neurogenesis [64] which can be attributed to its antidepressant action.…”
Section: Discussionmentioning
confidence: 99%